PELATIHAN OLAHAN SAWI HIJAU UNTUK MENUMBUHKAN JIWA WIRAUSAHA PADA KELOMPOK WANITA TANI MT AL MUHAJIRIN DI KELURAHAN TAMALANREA JAYA - Darwis, Khaeriyah; Anwar, Andi Rahayu (Universitas Muhammadiyah Tapanuli Selatan, 2018)
Training of the processed green mustard aims to build the entrepreneurship spirit of MT Al Muhajirin mothers with the utilization of processed green mustard food which, if developed to long-term, will foster a productive economy that can increase family income. Also, it is expected later KWT MT Al Muhajirin able to form a Trade Business that produces green mustard chips and ice cream. The activity of dedication to the community of KWT MT Al Muhajirin is done by the method of training in practice and theory. For two days, community members are invited to understand the purpose, benefits,and application of processed green mustard as nutritious food ingredients and economic value. Presentation of learning materials related to the importance of community empowerment through the independent learning process, this group is conducted by the material, objectives and practical benefits of each theme. In the last session, community service activities are presented demonstrations of cooking food, process the green mustardinto chips and ice cream is healthy, practical and favored by all walks of life. The process of processing the green mustard greens as raw materials for obtaining these types of food is done by the method of demonstration while providing explanations that must be mastered when will process the green mustard into healthy food for the family, and economic value.Â Keywords:Entrepreneurship, Green Mustard Processed, Green Mustard ice cream.